Interaksi Pengguna dan Jasa Pernikahan di Instagram Sebagai Alternatif Pencarian Informasi - Setyawati, Nur Janah Dwi (JURNAL BISNIS STRATEGI, 2020)
Instagram usability is to search for a person's profile, expand friendships, and offer a product between people. The study focused on the interaction between the user and the marriage provider to explain the process of acceptance of technology especially Instagram. The research question that is formed was â€œhow the interaction of East Jakarta brides and the wedding vendors on Instagram in planning their wedding so that behind the alternative wedding reference online?â€. The method used a netnography, and interviews, the informant has chosen in the East Jakarta area were five people. The research aims to understand how social media helps brides working in East Jakarta to plan weddings and construct diverse contributions from audiences. The results obtained Instagram is useful for all informant in making it easier to search for information related to wedding services. The information is